2021
DOI: 10.1186/s12906-021-03232-2
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic acid induces apoptosis and anoikis in colorectal carcinoma RKO cells

Abstract: Background Ursolic acid (UA) is an anti-cancer herbal compound. In the present study, we observed the effects of UA on anchorage-dependent and -independent growth of human colorectal cancer (CRC) RKO cells. Methods RKO cells were cultured in conventional and detached condition and treated with UA. Cell viability was evaluated by CCK-8 assay. Cell cycle was analyzed by flow cytometry. Apoptosis was identified by Hoechst 33258 staining and flow cytom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…However, all six cell lines treated with EPI showed evident bright blue, nuclear fragmentation, chromatin condensation, and formation of apoptotic bodies (Figure 4). Consistent with the results from the apoptosis assay, morphological analysis of the cancer cells after the treatment of H. leucospilota protein showed bright blue, nuclear fragmentation, and chromatin condensation, clear evidence suggesting apoptosis [28]; in contrast, morphological analysis did not show obvious morphological changes in any of the H. leucospilota protein treated normal cells. However, all six cell lines treated with EPI showed evident bright blue, nuclear fragmentation, chromatin condensation, and formation of apoptotic bodies (Figure 4).…”
Section: Effects Of H Leucospilota Protein Treatment On Inducing Cell...supporting
confidence: 82%
“…However, all six cell lines treated with EPI showed evident bright blue, nuclear fragmentation, chromatin condensation, and formation of apoptotic bodies (Figure 4). Consistent with the results from the apoptosis assay, morphological analysis of the cancer cells after the treatment of H. leucospilota protein showed bright blue, nuclear fragmentation, and chromatin condensation, clear evidence suggesting apoptosis [28]; in contrast, morphological analysis did not show obvious morphological changes in any of the H. leucospilota protein treated normal cells. However, all six cell lines treated with EPI showed evident bright blue, nuclear fragmentation, chromatin condensation, and formation of apoptotic bodies (Figure 4).…”
Section: Effects Of H Leucospilota Protein Treatment On Inducing Cell...supporting
confidence: 82%
“…Numerous treatments with natural products, such as herbal compounds, have been evaluated for their ability to induce cell apoptosis in crc (106)(107)(108)(109). Previous studies have assessed whether cell apoptosis is induced by UA in cancer, such as CRC and breast and esophageal cancer, via different mechanisms (27,110,111). The present study demonstrated that combined UA + DOX treatment promoted crc cell late apoptosis and increased the sub-G 1 apoptotic fraction as assessed by FITC/PI staining and flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
“…cytometry, UA and 5-FU were found to arrest the cell cycle at the G0/G1 phase, with a diminished proportion in the S phase (Figure 3A), consistent with another report. 21 Subsequently, the influence of UA on cell cycle-related gene expression was appraised. Intriguingly, UA concentration-dependently diminished mRNA abundance in c-Myc and cyclin D1 of SW620 cells (Figure 3B), consolidated by the western blotting, whose data suggested that UA also concentration-dependently mitigated protein expressions of c-Myc and cyclin D1 in SW620 cells (Figure 3C).…”
Section: Ursolic Acid Inhibits the Malignant Phenotype Of Human Crc C...mentioning
confidence: 99%